2018
DOI: 10.1021/acs.biomac.8b00282
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Hydrogels Based on Lignin-Methacrylate Copolymers with Enhanced Water Retention and Tunable Material Properties

Abstract: Synthesizing lignin-based copolymers would valorize a major coproduct stream from pulp and paper mills and biorefineries as well as reduce the dependence on petrochemical-based consumer goods. In this study, we used organosolv lignin isolated from hybrid poplar ( Populus trichocarpa × P. deltoides) to generate lignin-containing methacrylate hydrogels. The copolymer hydrogels were synthesized by first grafting 2-hydroxyethyl methacrylate (HEMA) onto lignin (OSLH) via esterification and then by free radical poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Poly(2‐hydroxyethyl methacrylate) (pHEMA) has been widely applied in biomaterials due to its biocompatibility and versatile polymer fabrication. Hydrogels containing pHEMA can absorb and hold significant quantities of water in their three‐dimensional network . Special attention has been paid to poly( N , N ‐dimethylacrylamide), which can be used as a hydrophilic component in copolymers .…”
Section: Resultsmentioning
confidence: 99%
“…Poly(2‐hydroxyethyl methacrylate) (pHEMA) has been widely applied in biomaterials due to its biocompatibility and versatile polymer fabrication. Hydrogels containing pHEMA can absorb and hold significant quantities of water in their three‐dimensional network . Special attention has been paid to poly( N , N ‐dimethylacrylamide), which can be used as a hydrophilic component in copolymers .…”
Section: Resultsmentioning
confidence: 99%
“…16 Our group has also recently demonstrated that engineered hydrogels containing methacrylatemodified hardwood lignin exhibited increase in water retention capacity and tunable mechanical properties. 17 Moreover, alkene-functionalized lignin was successfully harnessed for photo-induced polymerization reactions. 18 In short, these studies demonstrate that designing lignin building blocks via chemical modification of the OH groups is a feasible approach for formulating 3D printing resins with tunable properties.…”
Section: Introductionmentioning
confidence: 99%
“…We used a procedure for lignin acylation that we have reported previously [ 30 , 34 ], which is an adaptation of the method for syringyl methacrylate synthesis reported by Epps et al [ 35 ]. Briefly, one equivalent of either methacrylic anhydride or acrylic anhydride was mixed with lignin (1 equiv.…”
Section: Methodsmentioning
confidence: 99%